2012
DOI: 10.5307/jbe.2012.37.1.044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vibration Stress on the Quality of Packaged Apples during Simulated Transport

Abstract: Purpose:The characteristics of in-transit vibration stress and possible damage to packaged apples were examined. Methods: A simulated transportation environment with a specific power density profile was used for vibration impact experiments to determine the resulting decrease in packaged apple quality. Apples with or without vibration stress were stored at low temperature (5 ± 0.8℃, 75-85% relative humidity) for 30 days. Statistically significant differences (p ≤ 0.05) were found between apples with and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
1
14
0
5
Order By: Relevance
“…Jung and Park simulated a standard ASTM vibration profile for a total journey duration of 331 minutes, replicating the duration of the entire journey in transit to measure the effect on apples. This is not a practical approach in many transport scenarios, such as long‐duration interstate transport.…”
Section: Implications On Vibration Measurement and Simulationmentioning
confidence: 99%
“…Jung and Park simulated a standard ASTM vibration profile for a total journey duration of 331 minutes, replicating the duration of the entire journey in transit to measure the effect on apples. This is not a practical approach in many transport scenarios, such as long‐duration interstate transport.…”
Section: Implications On Vibration Measurement and Simulationmentioning
confidence: 99%
“…Regardless of vibration stress, the average increase in the soluble solids content of mangoes was 7.9 ºBrix at the end of the evaluations. Jung and Park (2012) observed that the soluble solids content of 'Fuji' apples increased significantly with storage time in all samples, with or without vibration stress, due to the conversion of starch into sugar. However, the increase was faster in apples subjected to vibration, which could be explained due to an increase in both temperature and enzymatic activity in the sugar transformation process, factors that possibly did not affect 'Palmer' mangoes with the same intensity.…”
Section: Evaluations During Storagementioning
confidence: 84%
“…Produk segar biasanya ditransportasikan melalui moda transportasi darat yaitu dari petani ke konsumen, dan yang harus diperhatikan bahwa produk segar tetap dalam kualitas terbaik dan dipertahankan kondisinya selama transportasi [4]. Kualitas buah dan sayuran dapat menurun selama transportasi karena terjadinya kerusakan fisik dan biologis yang disebabkan oleh getaran [5]. Beberapa peneliti menyatakan 25% produk segar hilang setelah panen, terutama selama pemanenan atau transportasi dari lapangan ke pasar jika tidak dengan pengemasan yang baik [6].…”
Section: Pendahuluanunclassified